2021
DOI: 10.1097/mpa.0000000000001830
|View full text |Cite
|
Sign up to set email alerts
|

Acute and Severe Acute Pancreatitis and the Effect of Cannabis in States Before and After Legalization Compared With States Without Legalized Cannabis

Abstract: Objectives: Cannabis legalization has increased its use. The incidence of acute pancreatitis (AP) and severe acute pancreatitis (SAP) has also increased. In this study, data on pancreatitis were obtained from 2 states before and after cannabis legalization and compared with 2 states without legalized cannabis.Methods: Data were extracted from State Inpatient Databases from the states of Colorado and Washington before recreational cannabis legalization (2011) and after legalization (2015). Arizona and Florida w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…[26] Studies have also shown that cannabis users who drink alcohol have decreased acute and chronic pancreatitis. [27] Alcohol increases the absorption of THC, and some cannabis users might consume less alcohol while consuming cannabis. Nair et al reported that alcohol abuse is associated with a higher level of inflammatory cytokines such as IL-10, IL-12, IL-15, IL-309, and GMCSF, while cannabis abuse has lower activation of these cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…[26] Studies have also shown that cannabis users who drink alcohol have decreased acute and chronic pancreatitis. [27] Alcohol increases the absorption of THC, and some cannabis users might consume less alcohol while consuming cannabis. Nair et al reported that alcohol abuse is associated with a higher level of inflammatory cytokines such as IL-10, IL-12, IL-15, IL-309, and GMCSF, while cannabis abuse has lower activation of these cytokines.…”
Section: Discussionmentioning
confidence: 99%